2021
DOI: 10.3390/s21041070
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Biceps Muscle Fatigue in Human Activity Recognition

Abstract: Nowadays, Human Activity Recognition (HAR) systems, which use wearables and smart systems, are a part of our daily life. Despite the abundance of literature in the area, little is known about the impact of muscle fatigue on these systems’ performance. In this work, we use the biceps concentration curls exercise as an example of a HAR activity to observe the impact of fatigue impact on such systems. Our dataset consists of 3000 biceps concentration curls performed and collected from 20 volunteers aged between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The second reason is that medium-weight dumbbells are often reported as the most commonly used dumbbells across gym-goers [54]. Third, in previous work, we found that the 4.5 kg weight dumbbell provides the best trade-off between number data points recorded in data sessions and time to reach fatigue during an exercise [55]. We use Borg's scale in our work because we believe that RPE is an appropriate marker of fatigue as previous studies within sport science have proven that RPE is capable of modeling a person's performance better in the real world compared to only heart rate monitoring [7,49,56].…”
Section: Dataset Descriptionmentioning
confidence: 82%
See 3 more Smart Citations
“…The second reason is that medium-weight dumbbells are often reported as the most commonly used dumbbells across gym-goers [54]. Third, in previous work, we found that the 4.5 kg weight dumbbell provides the best trade-off between number data points recorded in data sessions and time to reach fatigue during an exercise [55]. We use Borg's scale in our work because we believe that RPE is an appropriate marker of fatigue as previous studies within sport science have proven that RPE is capable of modeling a person's performance better in the real world compared to only heart rate monitoring [7,49,56].…”
Section: Dataset Descriptionmentioning
confidence: 82%
“…A recent study shows a significant performance improvement (from 89.83% to 96.62%) after utilizing deep learning in HAR systems [107]. We opt to use DT and ANN models in the current study to examine whether our personalization approach can mitigate the hindering effect of subject data variability encountered in our previous works [45,55]. So, since our findings seem encouraging, we have decided to use CNN in our future work to examine our personalization approach further.…”
Section: Future Workmentioning
confidence: 89%
See 2 more Smart Citations
“…Leave-one-out cross-validation (LOOCV) was used, where the number of folds equals the number of instances or subjects in the training set. In this case, 70% is equivalent to 21 subjects in the training data [74,75].…”
Section: Training and Validationmentioning
confidence: 99%